Metabolic and inflammatory links between metabolic dysfunction-associated steatotic liver disease and Alzheimer's disease - Gary Zhang (Environmental Disease)
Metabolic dysfunction-associated steatotic liver disease (MASLD) and Alzheimer’s disease (AD) are two growing epidemics across the globe. The two chronic, complex diseases have been increasingly linked through shared metabolic, inflammatory, and molecular pathways. Like many other complex diseases, MASLD and AD are caused by the interaction between genetic and environmental factors. Chronic inflammation and metabolic dysregulation, two hallmark features of MASLD and AD, are associated with pathological factors, such as insulin resistance, dyslipidemia, endoplasmic reticulum stress, and oxidative stress in both diseases. The liver’s inflammatory state can contribute to neurodegenerative processes in AD, and vice versa, the neuronal dysregulation caused by AD condition profoundly affects whole body metabolism, which can lead to fatty liver disease. This review aims to provide a brief view of the current understanding of the metabolic and inflammatory links between MASLD and AD and the molecular players underlying these pathological conditions.